Cleaning Up after the Log Drivers’ Waltz : Finding the Ottawa River Watershed - Benidickson, Jamie (Les Cahiers de droit, 2010)
The Ottawa River has experienced the environmental impact of a succession of industrial uses from the lumber trade through hydroelectric power development to pulp and paper manufacturing. Each of these activities, and the introduction of substantial discharges of urban wastewater, has been the subject of legal intervention and regulatory controls. The present paper surveys this largely sectoral approach to water quality protection along the Ottawa River and notes in conclusion tentative steps being taken to formulate a more comprehensive and coherent framework on a watershed basis.